Changes in the epidemiology of pediatric brain abscesses pre- and post-COVID-19 pandemic: a single-center study - Yuchen Liu; Zhenjiang Bai; Tianquan Yang; Bin Yuan; Yong Han; Yongjun Xiang; Ruxuan Zhou; Jingxuan Sun; Min Chen; Chuangli Hao; Hangzhou Wang (BMC, 2024)
Abstract Background An increased incidence of brain abscesses was observed post-COVID-19 pandemic. However, it remains unclear how the COVID-19 pandemic influenced the epidemiology of brain abscesses. This study aimed to investigate changes in the epidemiology of brain abscesses pre- and post-COVID-19 pandemic. Methods A retrospective study of demographic, clinical, radiological, and laboratory characteristics of patients with brain abscesses in Children's Hospital of Soochow University from 2015-2023 was performed. Results A total of 34 patients were admitted to the hospital during the study. The post-COVID-19 cohort had an average of 5.5 cases/year, which is a 129.2% increase compared to the pre-COVID-19 cohort's average of 2.4 cases/year. Additionally, the rates of fever upon admission (86.36% vs 50%, p = 0.04) and experiencing high-grade fever within 6 weeks before admission (40.91% vs 8.33%, p = 0.044) were significantly increased. A potential rise in the rate of intensive care unit admission was observed (36.36% vs 8.33%, p = 0.113). The average value of globulin in the post-COVID cohort was significantly higher compared to the pre-COVID cohort (31.60 ± 5.97 vs 25.50 ± 5.08, p = 0.009). Streptococcal infections were the predominant cause of brain abscesses in both cohorts (40% vs 43.75%, p = 0.57). Conclusions There was a significant increase in the number of brain abscess patients after the COVID-19 pandemic. This underscores the importance of children receiving the streptococcal vaccine.